The Effect of Dynamic Knee Valgus during Overhead Squat on Distal and Proximal Knee Joints Muscle Strength and Range of Motion in Basketball Player - Hemn Mohammadi; Hassan Daneshmandi; Mohammadhoein Alizadeh; Ali Shamsimajlan (Islamic Azad University, Hamedan Branch, 2018)
Objective: The purpose of this study was investigate the effect of dynamic knee valgus during overhead squat, on hip and ankle joints muscle strength and range of motion in basketball players. Methods: In this study 35 healthy basketball players (with the mean age 20.98± 1.99, height 183.27 ± 6.64 cm and mass 75.31 ± 9.24 kg), in the control group (n = 18) and dynamic knee valgus group (n = 17) with no lower-extremity injury during the last year were the volunteers. The peak force and the passive range of motion were measured rspecively by a hand-held dynamometer and a goniometer. The Independent T-test at the significance level of 0.05 was used to determine the difference of strength and range of motion in the control and dynamic knee valgus groups. Results: Compared by the control group, the dynamic knee valgus group showed to have a greater strength of the hip external rotation and extension (respectively P=0.000, P=0.004), smaller Plantarflextion strength (P=0.001), smaller dorsiflexion range of motion with knee bent (P=0.021), and greater external rotation of the hip (P=0.002). Conclusions: The results showed that the dynamic knee valgus group exhibited tight and weak ankle musculature, and as appeared, training interventions focused on improving strength and range of motion of the ankle can improve lower extremity kinematics of during overhead squat and modify dynamic knee valgus.